Strategies to Grow and Expand a Nonprofit Business - Awode, Olusegun; Anthony, Peter (International Journal of Emerging Trends in Social Sciences, 2020)
Nonprofit organizations make significant contributions to individuals, organizations, communities, the environment, and societies, but many do not survive in the long run. This study is important to business leaders in for-profit and nonprofit organizations who want to implement strategies for the long-term survival of their business, improve business performance, and effect positive social change. Grounded in Penrose’s theory of growth, the purpose of this qualitative single-case study was to explore strategies leaders used to grow and expand a nonprofit business in the midwestern region of the United States. The participants comprised 5 nonprofit leaders with recorded success at growing and expanding their business. Data were collected from semistructured interviews and document reviews involving the governance system, programs, strategies, operations, partners, and budget. Thematic analysis was used to analyze the data. Four themes emerged: strategic planning cycle, effective fundraising planning and strategy, resource and financial assessment, and team development and positive working conditions. A key recommendation includes that nonprofit leaders seeking growth and expansion engage in effective strategic planning. The implications for positive social change include the potential for leaders of nonprofit organizations to provide growth and expansion strategies to increase their organizations' capacity for positively transforming communities by maintaining or improving available opportunities and services.